The concept of GOD in works about the national liberation movement of the first half of the XX century - Bachun, Liliya (Current issues of Ukrainian linguistics: theory and practice, 2019)
The main concepts of theolinguistics, its history, actual state and prospects for the further development have been analyzed in this article.  Religious linguistics is currently in the process of establishing: not only Ukrainian, but also foreign, as a consequence of the post-Soviet Renaissance. A little researchness of a such young linguistic science, as theolinguistics, the formation of its methodology and a number of terms, the use of the writers theories in fiction works and their functional load formulate the relevance of the chosen topic. The motives of using the theonim «God» in the fiction and memoir works about the national liberation movement of the first half of the twentieth century have also been determined with its quantitative functioning in the texts. The variability of using the theonim «God» have been described in the article, as well as its functional load in constant expressions, phrases, verbal constructions. Despite the fact that the analyzed 19 fiction and memoir novels are mostly military and social oriented, and yet the concept of «God» is present in all works perfectly. Since Ukraine, thanks to St. Vladimir, is a Christian state, and actually was  Christian in 1917-1954, despite the prohibition of believing in God by the Soviet state, the texts mostly are  the most part, are the deities of the Christian belief. «God» as a single-element  proper name is mentioned approximately 228 times in the seven novels about the liberation movement of UPA. In addition, the anthroponimicon of the texts about the liberation period of 1917-1922 years (12 novels) counts 1930 units, where there are separately 135 references to the theonim «God». These numbers are not the final measure of the degree of the use of the theonim «God» in the analyzed novels, as we do not take into account its variants. To analyze the variability of the theonim «God» we point out the following subgroups: a) variants of the use of the theonim «God» in the texts of the novels: we have identified 10 variants of the use of the theonim «God» from 19 analyzed novels that writers point in the texts through the speech of the characters’ speech; b) reduced-caress names;c) gratitude to God and His praise; d) the use of the theonim to express a wish or a blessing; e) expression of hope in God's power; f) «God» as a way of expressing a cry in the sentence; g) the concept of «God» in theological texts, greetings, proverbs, which function in the texts of the analyzed novels.
Keywords: onomastics, religious linguistics, theonim, theolinguistic, stylistics.